The role of prenatal auditory stimulation in the development of filial behaviour in the domestic duckling - De Wet, John Manning (Department of Psychology, 2016)
The aim of the first three experiments was to delineate the physical characteristics of an artificial call for which naive Peking X Aylesbury ducklings show the greatest natural preference. In each experiment SO ducklings were tested at 20 ± 2 hrs. posthatching, for following and approach responses to one of four auditory stimulus conditions or a silent model. The responsiveness of subjects was greatest when the call contained tone frequencies of 500, 800, and 1600Hz and was presented at a repetition rate of 4/second with a note duration of 50 milliseconds (Optimal call). In Experiment 4 Peking X Aylesbury eggs were exposed to intermittent prenatal stimulation with the optimal call and the hatchlings were tested for responsiveness to this call at 20 ± 2 hrs. posthatching. Subjects with prenatal auditory experience of the optimal call showed significantly greater responsiveness to this call than non-stimulated control subjects. The aim of the final experiment was to determine whether the natural auditory stimulus preferences of ducklings could be overridden through sheer prenatal experience of a non-preferred call. Ducklings with prenatal experience of the non-preferred call continued to show as strong a preference for the optimal call as non stimulated control subjects. The responses of both stimulated and non-stimulated subjects to the optimal call were significantly stronger than the responses of stimulated and non-stimulated subjects to the non-preferred call. The responses of stimulated subjects to the non-preferred call were only slightly stronger than responses of non-stimulated subjects to the same call. These results indicate that responsiveness to calls for which naive birds show the greatest preference is enhanced by prenatal experience of the preferred call. This effect is not evident, however, when subjects are stimulated prenatally with a non-preferred call.